2018
DOI: 10.3892/ol.2018.7949
|View full text |Cite
|
Sign up to set email alerts
|

Rab23 promotes the cisplatin resistance of ovarian cancer via the Shh-Gli-ABCG2 signaling pathway

Abstract: Abstract.As a novel member of the Rab GTPase family, the role of Rab23 has been reported in multiple types of tumor. However, to the best of our knowledge, the role of Rab23 in ovarian cancer (OC) has not yet been reported. In the present study, immunohistochemistry analysis demonstrated that Rab23 was upregulated in OC tissue; survival analysis indicated that Rab23 expression was associated with a reduced overall survival (OS) rate and disease-free survival (DFS) time. In vitro experiments also demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…Subsequently, RAB23 was a target to inhibit drug resistance and improve the prognosis of patients with ovarian cancer [14]. However, as far as we know, the role of miR-597-3p in thyroid carcinoma and its relationship with RAB23 has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, RAB23 was a target to inhibit drug resistance and improve the prognosis of patients with ovarian cancer [14]. However, as far as we know, the role of miR-597-3p in thyroid carcinoma and its relationship with RAB23 has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that Hh signaling via Smoothened and GLI1 requires involvement of the RAB family ( 31 ). RAB23 interacts with GLI1 to promote the progression of tumors such as breast, prostate, and ovarian cancers ( 32 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that Hh signaling pathway is correlated with MDR in various cancers. 11,21,22 However, the relationship between Hh signaling pathway and OSCC is unclear. Thus, further investigation into the potential role of Hh signaling pathway in the MDR of OSCC is required.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another report revealed the detectable interaction between SHH-GLI1-ABCG2 pathway and drug resistance in ovarian cancer. 22 As a downstream molecule of SHH signaling pathway, ABCB2 contributes to the drug resistance of pancreatic ductal adenocarcinoma cells. 28 that activation of the Hh signaling pathway upregulated expression of ABCG2 in lymphoma, which is consistent with our data.…”
Section: Discussionmentioning
confidence: 99%